Left ventricular noncompaction: the importance of identifying high-risk patients within the scope of left ventricular hypertrabeculation. (14th October 2021) - Viegas, J M; Rosa, S A; Bras, P; Castelo, A; Ferreira, V; Gameiro, F; Rio, P; Abreu, J; Timoteo, A T; Galrinho, A; Branco, L M; Ferreira, R C
Abstract: Introduction: Prominent left ventricular (LV) trabeculation is frequently encountered, however LV noncompaction (LVNC) criteria are not always fulfilled. The clinical and prognostic significance of these findings remains unclear. Objectives: To characterize the patients (P) with echocardiographic suspicion of LVNC and to assess clinical outcomes. Methods: Retrospective single-centre study that included all echocardiograms between January 2018 and June 2020 perceiving LV hypertrabeculation. The cohort underwent diagnostic assessment for LVNC by Chin and Jenni criteria. Baseline characteristics were evaluated. Composite endpoint of cardiovascular death, heart failure (HF) hospitalization, ventricular arrythmias (VA) and nonfatal stroke was considered. Results: 51P, 75% male, mean age 50±18 years. 35P (69%) had associated heart conditions, of which 57% had other known cardiomyopathy (mainly dilated cardiomyopathy), 14% congenital, 26% ischemic and 3% valvular heart disease. 2P were in postpartum period and 1P was an athlete. Family history of cardiomyopathy was present in 8P (16%). 12P underwent genetic testing, with TTN and MYH7 mutations being the most frequently detected. Prior clinical HF was reported in 53%, previous stroke in 14%, and non-sustained and sustained VA in 24% and 4%, respectively. Mean NYHA classification was 1.8±0.7, with 31% being asymptomatic. The prevalence of LVNC by Chin criteria was 31% and by Jenni criteria was 55%. 32P (63%) met at least one LVNC criteria. This group was younger (45±18 vs 59±15, p=0.004), had higher NT-proBNP levels (3644±2819 vs 389±640, p=0.048) and QRS fragmentation (59% vs 21%, p=0.027). Significantly higher LV end-diastolic volume (84 (41) vs 64 (28)ml/m 2, p=0.008) and end-systolic volume (51 (37) vs 35 (20)ml/m 2, p=0.004), along with lower LV ejection fraction (39±12 vs 49±13%, p=0.009) and global longitudinal strain (−11±5 vs −17±4%, p=0.003) were noticed. P who met LVNC criteria also had higher number of affected LV segments (6.4±1.8 vs 4.2±1.6, p<0.001). Over a mean follow-up of 18±9 months, the incidence of composite endpoint was 35%. Univariate Cox analysis showed a significant association between the presence of LVNC criteria and adverse outcomes (HR: 5.108, 95% CI: 1.682–11.236, p=0.030) (Fig. 1). Conclusion: LV hypertrabeculation can be encountered in a variety of clinical scenarios and often overlaps with other heart diseases. P satisfying criteria for LVNC had more impairment in LV performance and worse clinical outcomes. FUNDunding Acknowledgement: Type of funding sources: None.